ANALYZING THE RELIGIOUS PRACTICES AMONG THE ELECTRICAL MOTOR INSTALLATION DEPARTMENT STUDENTS IN SMKN 2 PEURELAK ACEH TIMUR - Sadrina sadrina; Muhammad Ichsan M. Nasir; Irma Nova Asriyanti (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
Education is a conscious effort to create a learning process atmosphere which students actively develop their potential. Religious value education is very closely with humans’ character. The aim of the study was to assess the implementation of religious practice in the SMKN 2 Peurelak. The design of the study is kind of Pre-Experimental design with qualitative approach. The experiment class used was an Electrical Motor Installation Department, class X, XI, and XII. However, for the interview needed, the participants involved were four students from different classes and two teachers. The instrument used in the study was a set of the interview protocol. This qualitative method would be analyzed by encoding the respondents’ initials and their transcripts. The transcript will be analyzed by identifying emerging themes. The finding result showed that the students sensed their spirit and motivation were increased after the implementation of religious activities in their school. They asserted feeling calm in heart, more concentrated on studying and well-disciplined between learning and play.